Evolution of a serie the inferior member amputation - Croci, Fabio; Gastambide, Carmelo; Perrier, José Pedro; Ríos, Miguel; Pérez Penco, Ernesto; Gateño, Nisso (Cirugía del Uruguay, 1983)
On oportunity of a serie of 85 arteritic patients, 106 inferior member am putations were performed , and authors studied its inmediate and diferred evolution. F,·ecuency of bad results and necessity of reamputations is remarked. lts severity in diabetic patient is remarked. . Mortality was of 8,2º/o.